New Look at Soft Skills Development Through Debate Technology - Blyznyuk, Tetyana (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
The article highlights theoretical and practical aspects of the relevant contemporary issue of development of soft skills of pre-service primary school teachers by means of intensification of debate in the classroom. Modern society requires from specialists not only deep knowledge in their fields, but also the ability to effectively communicate and interact with others. Soft skills development through debate technology is a contemporary and innovative approach to enhancing essential interpersonal and communication skills. Debate technologies contribute to the development of argumentation skills, the ability to listen, respond to the arguments of opponents and express one's opinions clearly and convincingly. The approach combines the traditional practice of debate with modern technology to provide a more engaging and effective learning experience. The author analyses the problem from two perspectives: development of students’ soft skills, on the one hand, and pedagogical potential of debate in this context, on the other. The definition of the concepts “soft skills” vs “hard skills” is generalized, the factors of efficient application of debate technologies are outlined. The researcher proved that ability to arrange engaging debate in different academic courses at the university is a characteristic feature of professional competence of an innovative educator as it helps develop students’ key skills. The formation of the latter takes place both in individual subjects teaching and in the process of subjects’ integration.